Administration of Insil Baru Village, Passi Timur Sub-district, Bolaang Mangondow Regency - Fitri Mamonto; Sita Mokoginta; Leidy Wendy Palempung; Jolanda E. Kaihatu; Irfan Rifani (Technium Social Sciences Journal, 2024)
This research aims to analyze and describe the administration of the new village government. The research method used is descriptive qualitative. The number of informants in this study was 5 people. Data collection uses observation, interview and documentation techniques. Data analysis through data reduction, data presentation and drawing conclusions. The research results show that based on research conducted by researchers, it can be concluded that not everything can be implemented. Among them are 27 village administrations according to PERMENDAGRI No. 47 of 2016 and it was found that there are 3 village administrations that have not been implemented, namely the development activity book, development results inventory book and activity support cash book. The cause of the obstacles to implementing this administration is the lack of technical guidance from the government districts about how they should manage village administration, then the lack of tools needed to manage village administration.